Towards an integrated water management: Comparing German and Dutch water law from a spatial planning perspective - Hartmann, Thomas; Spit, Tejo (International Journal of Water Governance, 2015)
Water management increasingly deals with spatial aspects; spatial planning interferes and depends in various ways on water management. Particularly in urban areas, this interference calls for an integrated water management. As a result, water management and spatial planning meet. Laws frame the interaction of the two institutions. In this contribution, Dutch and German water law are compared in terms of the governance for water management they nurture and sustain. A conceptual framework by Driessen et al. is applied, which incorporates analysing three characteristics of governance: the actor relations, the institutional context, and the approaches to the governance object – water – itself (Driessen et al., 2012). Finally this contribution aims to reveal the relation between modes of governance and the law, and it makes a claim for governance research: law matters.